ISLAMIC WORK ETHICS DALAM PENINGKATAN MUTU KERJA SUMBER DAYA INSANI PT. BANK MUAMALAT INDONESIA CABANG MAKASSAR - Megawaty; Hendra Gunawan; Paris Dauda (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
This study aims to analyze Islamic Work Ethics in Improving the Quality of Work of PT. Bank Muamalat Indonesia, Tbk Makassar Main Branch Office (Case Study of Human Resources). The method of analysis used in this research is qualitative research methods. The subject of research is the application of Islamic work ethics in improving the quality of work of employees, especially frontliners based on indicators of improving the quality of employee work with Muamalat IDEAL (Modern Professional Islamic). The results showed that Islamic work ethics plays a role as a basis in improving the quality of work of employees, especially frontliners. Keywords: Islamic Work Ethics, Work Quality, Human Resources